Aga Khan historic cities programme - Jodidio, Philip (New York Prestel, 2011)
The Aga Khan Historic Cities Programme promotes the conservation and re-use of buildings and public spaces in historic cities in the Muslim World as a catalyst to improving the quality of life of their inhabitants. This book presents more than 30 case studies that illustrate the Programme's efforts to spur social, economic, and cultural development in sustainable ways. In countries such as Afghanistan, Egypt, India, Mali, Pakistan, Syria, Tajikistan and Tanzania the Historic Cities Programme has gone beyond restoration to address the questions of the social and environmental context, adaptive re-use, institutional sustainability and training. Recent photographs filled with brilliant detail; precise maps, drawings and technical data; and expert essays on urban planning, collaborative networks, parks and gardens, and sustainability are included in this exciting book on the work of one of the Muslim world's most successful proponents of cultural conservation.
Keywords: ARCHITECTURE CONSERVATION (AR-CONS)